Mahabbah dan Fana: Analisis Makna Asosiatif Lagu “Tanpa Aku” Karya Panji Sakti - Haq, Dwiarni Dzakiratul; Fikra, Hidayatul (Fakultas Ushuluddin UIN Sunan Gunung Djati Bandung, 2024)
Music has an important role as a medium of emotional expression and spirituality, including in conveying deep messages that are full of meaning. The song “Tanpa Aku” by Panji Sakti raises the theme of spirituality which is often interpreted differently by listeners. This research aims to analyze the associative meaning of the song “Tanpa Aku” and its relationship with the concepts of mahabbah and fana'. This research uses a qualitative approach with a descriptive-analytical method to explore the symbolism and meaning in the song lyrics. The results of the analysis show that the associative meanings studied include: 1) Connotative Meaning; 2) Social Meaning; 3) Affective Meaning; 4) Reflective Meaning; 5) Collocative Meaning. In general, it was found that the associative meaning of this song refers to the spiritual journey of a servant who seeks to go to his Lord and escape from all the hustle and bustle of the world. The deep love for God and the release of ego and complete surrender to Him make this song full of mahabbah and fana' concepts in Sufism. This research concludes that this song not only contains aesthetic value, but also has potential as a medium for emotional and spiritual therapy.